STRENGTHENING INTERCULTURAL COMMUNICATION SKILLS OF HOTEL RECEPTIONISTS THROUGH A COMMUNITY-BASED TOURISM APPROACH IN LANTA NICE BEACH RESORT, THAILAND - Meerah Siwa; Abdul Rohim; Tiktik Dewi Sartika; Tami Alruby (Community Services and Social Work Bulletin, 2025)
Intercultural communication competence is essential for hotel receptionists working in multicultural tourism destinations. This study examines how community-based tourism (CBT) principles can strengthen intercultural communication skills among receptionists at Lanta Nice Beach Resort, Thailand. Using a qualitative case study approach, data were collected through in-depth interviews, observational notes, and document analysis related to guest interactions and cultural events. The findings show that CBT-oriented engagement enhances receptionists’ cultural awareness, communication adaptability, and problem-solving abilities when serving international guests. Participation in cultural activities, such as Christmas and New Year events, also facilitates reciprocal cultural learning between staff and visitors. Improved intercultural competence contributes to higher service quality and a more culturally inclusive guest experience. This study highlights the potential of CBT as a capacity-building strategy for frontline hospitality workers and offers insights for resorts seeking to strengthen guest satisfaction and promote sustainable tourism practices.